A Puzzle with Missing Pieces: Explaining the Effectiveness of World Bank Development Projects. (12th July 2022) - Ashton, Louise; Friedman, Jed; Goldemberg, Diana; Hussain, Mustafa Zakir; Kenyon, Thomas; Khan, Akib; Zhou, Mo
Abstract: The identification of key determinants of aid effectiveness is a long-standing question in the development community. This paper reviews the literature on aid effectiveness at the project level and then extends the inquiry in a variety of dimensions with new data on World Bank investment project financing. It confirms that the country institutional setting and quality of project supervision are associated with project success, as identified previously. However, many aspects of the development project cycle, especially project design, have been difficult to measure and therefore under-investigated. The paper finds that project design, as proxied by the estimated value added of design staff, the presence of prior analytic work, and other specially collected measures, is a significant predictor of ultimate project success. These factors generally grow in predictive importance as the income level of the country rises. The results also indicate that a key determinant of the staff's contribution is their experience with previous World Bank projects, but not other characteristics such as age, education, or country location. Key inputs to the project production process associated with subsequent performance are not captured in routine data systems, although it is feasible to do so. Further, the conceptualization and measurement of the success of project-based aid should be revisited by evaluative bodies to reflect a project's theorized contribution to development outcomes.